Commercial scale genetic transformation of mature seed embryo explants in maize - Ye, Xudong; Shrawat, Ashok; Williams, Edward; Rivlin, Anatoly; Vaghchhipawala, Zarir; Moeller, Lorena; Kumpf, Jennifer; Subbarao, Shubha; Martinell, Brian; Armstrong, Charles; Saltarikos, M. Annie; Somers, David; et al. (Frontiers in Plant Science, 2022)
A novel, efficient maize transgenic plant transformation system was developed using Agrobacterium-mediated direct transformation of embryo explants from mature seeds. Seeds from field grown plants were sterilized and crushed. The embryonic explants consisting of the coleoptile, leaf primordia, and shoot apical meristem were purified from the ground seed particles. The accessibility of meristematic cells within the seed embryo explants (SEEs) by Agrobacterium was enabled by pretreatment of the explants by centrifugation in the presence of Agrobacterium. Transgenic plants were obtained by multiple bud induction on high cytokinin media, followed by plant regeneration on hormone-free medium. Three different selectable markers were successfully used (cp4 epsps, aadA, and nptII). Stable integration of transgenes into the maize genome was demonstrated by molecular analyses. Germline transmission of the inserted transgenes to the next generation was confirmed by pollen segregation and progeny analysis. Phenotypic evidence for chimeric transgenic tissue was frequently observed. Chimerism was significantly reduced by including a second bud induction step with optimized cytokinin concentration and duration. Additional improvements, including culturing explants at an elevated temperature during bud induction led to the development of a revolutionary system for efficient transgenic plant production and genome editing. To our knowledge, this is the first report of successful transgenic plant regeneration through direct, Agrobacterium-mediated transformation of maize mature SEEs. This system starts with mature seed that can be produced in large volumes and the SEEs explants are storable. It has significant advantages in terms of scalability and flexibility over methods that rely on immature explants.